Kepemimpinan Ketua Program Studi Dalam Pengembangan Sumber Daya Manusia Berbasis Budaya Minangkabau - Lantika, Fani; Maryadi, M. (Universitas Muhammadiyah Surakarta, 2018)
The purpose of this study is to describe the characteristics of the Leadership preparation of the Chair of the Study Program in the development of human resources (HR) based on Minangkabau culture, the characteristics of leadership implementation Chair of the Study Program in the development of human resources (HR) based on Minangkabau culture, and leadership control characteristics in the development of human resources (HR) based on Minangkabau culture. The type of research used is qualitative using ethnographic design. The source of research data is the chair of the study program, lecturers, educational staff and students. Data collection techniques are carried out by interviews, observation, and documentation. Data were analyzed through the stages of data collection, data reduction, data presentation, and conclusion drawing. The results of the study can be concluded that (1) preparation for the development of lecturer human resources, refers to the implementation of the quality of lecturerstheoretically and practically. The activity prepared for the development of humanresources education personnel is through training in the administration of workthrough the development of educational human resources, HR mentoring and HRCoaching. Preparation of activities in the development of student human resourcesis through intra-curricular and extracurricular programs, (2) the implementationof lecturer human resource development, carried out in the form of curriculumevaluation, implementation of the Higher Education Tridharma, collaboration withother institutions or agencies, and further study of the lecturer Doctoral Program.The implementation of the development of human resources in human resources is carried out through the development of general competencies, the development of functional competencies, and the development of managerial competencies ofeducation personnel. The implementation of activities in the development of student human resources is through intra-curricular and extracurricular programs, and (3) controlling the development of lecturer human resources, carried out through the lecturer workload (BKD. Control in the development of human resources education personnel is through review and control of the work of educational staff in managing the correspondence, filing, and making work reports of education personnel every day Control in the development of student human resources is through PBM monitoring documents provided by education personnel Other controls are required for students to make reports, after extracurricular activities have been completed.